2021
DOI: 10.1155/2021/1579746
|View full text |Cite|
|
Sign up to set email alerts
|

Health Recognition Algorithm for Sports Training Based on Bi-GRU Neural Networks

Abstract: The healthcare benefits associated with regular physical activity recognition and monitoring have been considered in several research studies. Regular recognition and monitoring of health status can potentially assist in managing and reducing the risk of many diseases such as cardiovascular disease, diabetes, and obesity. Using healthcare equipment in hospitals, people can conduct regular physical examinations to check their health status. However, most of the time, it is difficult to reach a specific medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Table 1 Gated recurrent unit (GRU) is a variant of the LSTM network. GRU merges the LSTM input gate and the forget gate into the update gate and merges the data unit state and the hidden layer state [31], which realizes the simplification of the network structure. Like the LSTM network, GRU can capture the preceding information quickly, process variable-length sequences and significantly suppress diffusion and explosion of gradients.…”
Section: Feature Sequence Extraction (Cbam-cnn)mentioning
confidence: 99%
“…Table 1 Gated recurrent unit (GRU) is a variant of the LSTM network. GRU merges the LSTM input gate and the forget gate into the update gate and merges the data unit state and the hidden layer state [31], which realizes the simplification of the network structure. Like the LSTM network, GRU can capture the preceding information quickly, process variable-length sequences and significantly suppress diffusion and explosion of gradients.…”
Section: Feature Sequence Extraction (Cbam-cnn)mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%